Implementation of Think Pair Share (TPS) Cooperative Learning Model to Improve Mathematical Connection Ability - Rozak, Abdul; Qohar, Abd (Journal of Education Reseach and Evaluation, 2021)
This article aims to describe the application of Think Pair Share (TPS) cooperative learning models to improve students 'mathematical connection abilities on derivative material. The mathematical connection indicators in this study are (1) the ability of mathematical connections between mathematical topics, (2) the ability of mathematical connections with other subjects, (3) the ability of mathematical connections with problems in daily life. This research is a class action research (CAR) conducted in class XI-G4 SMA Negeri 5 Malang in two cycles. The first cycle was carried out in five meetings, four meetings for the implementation of learning and one meeting for the final test of the first cycle. Whereas in the second cycle held in five meetings, namely four meetings for the implementation of learning and one meeting for the final test of the second cycle. The results of the research showed that an increase in students' mathematical connections from cycle I to cycle II was indicated by an increase in the grade average and the percentage of completeness in class learning. The classical average in cycle I was 82.79 and increased by 8.56 to 91.35 in cycle II, and the percentage of completeness in cycle I was 70.59% from 34 students and increased by 11.76% to 82.35% of 34 students in the second cycle.